DERMATITIS KONTAK AKIBAT KERJA PADA PENATA RAMBUT - Shirley M. Oslan; Made Bratiartha (Universitas Udayana, 2013)
Reports from dermatologist, there is an increasing rate of occupational contact dermatitis from years to years. Occupational contact dermatitis, based on its pathophysiology, can be divided into allergic contact dermatitis and irritant contact dermatitis. Unfortunately both have a similar clinical presentation that sometimes difficult to differentiate, but a precise diagnosis is needed to give the most effective treatment. Hairdressers placed in the third rank in the most highly risk occupation for occupational contact dermatitis. Proper identification on tools and materials used in each occupation, method of working, and other risk factors is needed in order to prevent occupational contact dermatitis, for hairdressers in particular.